CRITICAL AND SOCIAL MESSAGES IN BOOKS (ANALYSIS OF QUALITATIVE CONTENTS ON THE "POSITIVE" FOR ASA BOOK "WORKS ITA SEMBIRING) - Rosna Meylani Tampubolon; Lalita hanief; Muhammad Alif (Metacommunication, 2018)
“Positif! Nada untuk Asa” is a novel that contain many criticism and social message. It needed tarther research, so the result could improve the knowledge and become a refrence for the reader. The aim for this research was to find out the criticism anda social message content analysis about the from of self revealing and self concept of a people Living With HIV/AIDS (PLHIV) based on a novel “Positif! Nada untukAsa” written by Ita Sembiring.Data collection used data reduction, data serving anda data verification.This research used qualitative content analysis approach with descriptive type. For data analysis used analysis qualitative data. The theory that used in this research is the theory of interpersonal self disclousure stated by Josep A. Devito.there are 31 social messages and 22 messages such criticism in the novel.The result showed, a lot of the sentence contains the criticism anda social message, this book has explicit and implicit meaning which affect the self disclousure and self concept of PLHIV. There are 3 risk of self disclousure and these risk constructed by units such as words, phrase, and the realition between those units. there are 31 social messages and 22 messages such criticism in the noveKeywords: Novel, Criticsm and Social Message, HIV/AIDS